# Solve for n 3n^2=-6n-2

3n2=-6n-2
Add 6n to both sides of the equation.
3n2+6n=-2
Move 2 to the left side of the equation by adding it to both sides.
3n2+6n+2=0
Use the quadratic formula to find the solutions.
-b±b2-4(ac)2a
Substitute the values a=3, b=6, and c=2 into the quadratic formula and solve for n.
-6±62-4⋅(3⋅2)2⋅3
Simplify.
Simplify the numerator.
Raise 6 to the power of 2.
n=-6±36-4⋅(3⋅2)2⋅3
Multiply 3 by 2.
n=-6±36-4⋅62⋅3
Multiply -4 by 6.
n=-6±36-242⋅3
Subtract 24 from 36.
n=-6±122⋅3
Rewrite 12 as 22⋅3.
Factor 4 out of 12.
n=-6±4(3)2⋅3
Rewrite 4 as 22.
n=-6±22⋅32⋅3
n=-6±22⋅32⋅3
Pull terms out from under the radical.
n=-6±232⋅3
n=-6±232⋅3
Multiply 2 by 3.
n=-6±236
Simplify -6±236.
n=-3±33
n=-3±33
The final answer is the combination of both solutions.
n=-3-33,-3+33
The result can be shown in multiple forms.
Exact Form:
n=-3-33,-3+33
Decimal Form:
n=-0.42264973…,-1.57735026…
Solve for n 3n^2=-6n-2

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top